2020
DOI: 10.1097/spv.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Injection Technique for Extended-Release Local Anesthetic After Posterior Colporrhaphy and Perineorrhaphy: A Randomized Controlled Study

Abstract: Objectives To evaluate the effect of vaginal intraoperative infiltration of liposomal bupivacaine on vaginal pain among patients undergoing posterior colporrhaphy and perineorrhaphy. Methods This was a randomized, placebo-controlled trial offered to women undergoing posterior colporrhaphy and perineorrhaphy with concomitant pelvic reconstructive procedures. Liposomal bupivacaine or normal saline placebo (30 mL) was injected into the posterior vaginal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…During the full‐text screening process, 52 citations were excluded for the following reasons: irrelevant comparator or intervention (n = 7), did not report wound infiltration (n = 24), not being an RCT (n = 18), lack of available data (n = 2), or being an animal study (n = 1). Twenty‐two studies were included in this meta‐analysis 15‐18,28‐45 . A flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the full‐text screening process, 52 citations were excluded for the following reasons: irrelevant comparator or intervention (n = 7), did not report wound infiltration (n = 24), not being an RCT (n = 18), lack of available data (n = 2), or being an animal study (n = 1). Twenty‐two studies were included in this meta‐analysis 15‐18,28‐45 . A flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that qualified for inclusion, surgeries were performed under general anaesthesia in 12 studies 16,18,28‐34,37,43,45 and under local anaesthesia in 10 15,17,35,36,38‐42,44 . The time of wound infiltration was the period before skin incision in three studies, 34,38,42 and the period before skin closure in 19 studies 15‐18,28‐33,35‐37,39‐41,43‐45 . For the surgical method, five studies with patients undergoing minimally invasive surgery, 34,36,40,42,45 15 studies with patients undergoing open surgery 15,16,18,28‐33,35,37‐39,43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Injecting 20 mL of liposomal bupivacaine versus placebo into the lateral vaginal walls/levator muscle areas and perineal body immediately after posterior colporrhaphy, colpocleisis, sphincteroplasty, or perineorrhaphy, this study showed no reduction in postoperative pain. Finally, in a recent study by Evans et al, 13 a 30-mL mixture of 20 mL of liposomal bupivacaine and 10 mL of normal saline was injected into the posterior vaginal compartment and perineal body after posterior colporrhaphy and perineorrhaphy. No differences were found in postoperative pain, time to first bowel movement, passage of postoperative voiding trial and days to passed voiding trial, length of stay, or narcotic use.…”
Section: Discussionmentioning
confidence: 99%